Improving Student Learning Outcomes Through the Flipped-Project Based Learning Model: An Experimental Study - Abdul Bashith; Saiful Amin; Sri Mindarti; Muchammad Akbar Kurniawan; Sari Dewi; Ramadhani Lausi Mkumbachi (Institut Agama Islam Negeri Ponorogo, 2024)
This study aims to determine the effectiveness of the Flipped-Project-based Learning model on student learning outcomes. This type of quasi-experimental research uses a control group pretest-posttest design that is applied to class XI IPS SMA Negeri 8 Malang, Indonesia (social sciences program at State Senior High School) academic years 2023-2024. The instrument used is an essay test of 5 questions on International Economic Cooperation material that has been tested for validity and reliability. Data analysis used tests of normality, homogeneity, and independent sample t-test. The result of the study showed that the Flipped-Project Based Learning model was effective in improving students' student learning outcomes in Economics Lessons. Recommendations for further research, it is necessary to develop a project-based model in a blended or hybrid model by utilising digital learning or e-learning platforms.